Vismodegib for the treatment of radiation-induced basal cell carcinoma – a case report and brief literature study - Laliscia, Concetta; Baldaccini, Davide; Antonuzzo, Andrea; Paiar, Fabiola (Contemporary Oncology/Współczesna Onkologia, 2019)
Vismodegib is playing an increasing role in the treatment of locally advanced or metastatic basal cell carcinoma (BCC) that is not a candidate for surgery or radiotherapy, and also in radiation-induced BCC. A 22-year-old man with a history of Hodgkin lymphoma, nodular sclerosis stage IIA, from October 1994 to February 1995 treated with 25 mg/m² doxorubicin, 10 IU/m² bleomycin, 6 mg/m² vinblastine, and 375 mg/m² dacarbazine for four cycles, followed by conformal beam radiotherapy (EBRT) on laterocervical, supraclavear, and mediastinal nodes up to a total dose of 30 Gy and following EBRT boost on mediastinal nodes up to a dose of 10 Gy. Subsequently, the patient underwent conformal EBRT on lomboaortic nodes up to total dose of 30 Gy at the University Hospital of Pisa until May 1995. There was no evidence of disease, until March 2012 when the patient developed several BCCs, occurring in the field of prior radiation, treated with local excisions. No mutations of Hedgehog (Hh) pathway or other genes were found and nevoid basal cell carcinoma syndrome was not diagnosed. In February 2018, the patient began therapy with vismodegib at standard dose of 150 mg orally daily and was treated for 10 months, with low adverse events and with pathological complete response of disease until July 2019. This experience shows that there are, however very few, BCCs not associated with genetic disorders. Vismodegib seems to be an effective and safe therapeutic approach also for radiation-related BCCs, associated with relatively low toxicity.